Study on tribological behavior of biodiesel – Diethyl ether (B20A4) blend for long run test on compression ignition engine. (15th October 2018) - Chourasia, Sajan; Patel, Paresh D.; Lakdawala, Absar; Patel, Rajesh N.
Graphical abstract: Highlights: LCA of 512 h is conducted on CI engine fueled with diesel and B20A4. The wear in terms of dimension & weight measurement is carried out. The lube oil analysis using AAS and Ferrography is carried out. The comparisons of surface wear is presented as surface roughness plots. A regression model is proposed to predict wear of the engine. Abstract: The gradual reduction of world petroleum reserves, growths in prices of petroleum-based fuels and environmental pollution has increased attention to the search for unconventional fuels such as biodiesel. It has remained the focus of extensive amount of research since it is renewable and reduces the emission of pollutants. Though, some of the significant issues like compatibility of biodiesel with the crankcase lube oil, thermal stability of lube oil with biodiesel, changes in physical and chemical properties of lubricating oil with biodiesel etc. have not been adequately inspected. These requirements are to be addressed in order to confirm the long-term suitability of biodiesel in a current family of diesel engines. In the present work, these problems are addressed. With an overall objective of life cycle analysis, a long run endurance test (512 h) is carried out on CI engines fuelled with diesel and the optimized blend of bio-diesel fuel (B20A4) respectively. The endurance tests are directed as per IS 10, 000 for the examination of wear of engine components, lubricant's properties, suspended impurities, and wear metal debris. The wear of the various component of the engine is characterized by dimension and weight measurements. Lube oil analysis (Atomic Absorption Spectroscopy – AAS, Ferrography) were performed on oil samples, taken after every 128 h. The oil analysis suggested that the wear of B20A4 fuelled engine is substantially lower compared to the diesel. A regression model was also proposed to predict wear of the engine. The proposed regression model can be taken one step further to predict the overall wear of the engine. The total concentration of various metals debris collected in the lube oil sample (predicted using regression model) was found to be 640 mg/kg and 420 mg/kg for diesel and B20A4 respectively.